2015
DOI: 10.1021/ac504260t
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of DNA by Magnetic Ionic Liquids: Tunable Solvents for Rapid and Selective DNA Analysis

Abstract: DNA extraction represents a significant bottleneck in nucleic acid analysis. In this study, hydrophobic magnetic ionic liquids (MILs) were synthesized and employed as solvents for the rapid and efficient extraction of DNA from aqueous solution. The DNA-enriched microdroplets were manipulated by application of a magnetic field. The three MILs examined in this study exhibited unique DNA extraction capabilities when applied toward a variety of DNA samples and matrices. High extraction efficiencies were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(121 citation statements)
references
References 42 publications
1
119
0
1
Order By: Relevance
“…Under this scenario, Clark et al 302 tested first a triad of hydrophobic magnetic ILs ([N (C7H7)888 ][FeCl 3 Br], [P 666 14 ][FeCl 4 ], and [(C 7 H 7 )C 16 im-C 12 -(C 7 H 7 )C 16 im][NTf 2 ][FeCl 3 Br]) to induce phase separation in aqueous solution. 302 Further optimization studies, performed with standard salmon DNA, led to the conclusion that the dispersive droplet extraction is more efficient (79.3% vs 63.1%) and faster (5 s vs 120 min) than the single droplet mode and that only very low amounts of IL (ca. 10 μL) and mild pH conditions are needed.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…Under this scenario, Clark et al 302 tested first a triad of hydrophobic magnetic ILs ([N (C7H7)888 ][FeCl 3 Br], [P 666 14 ][FeCl 4 ], and [(C 7 H 7 )C 16 im-C 12 -(C 7 H 7 )C 16 im][NTf 2 ][FeCl 3 Br]) to induce phase separation in aqueous solution. 302 Further optimization studies, performed with standard salmon DNA, led to the conclusion that the dispersive droplet extraction is more efficient (79.3% vs 63.1%) and faster (5 s vs 120 min) than the single droplet mode and that only very low amounts of IL (ca. 10 μL) and mild pH conditions are needed.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…(i) Kill bacteria (O'Toole et al 2012); (ii) Extract, purify, and even store DNA at ambient temperature (Clark et al 2015(Clark et al , 2016; (iii) Stabilize proteins and enzymes Venkatesu 2014, Kumar et al 2017); (iv) Assist or prevent protein amyloidogenesis, and in some cases even return amyloid fibers to functional proteins (Byrne et al 2007, Byrne and Angell 2008, 2009);…”
Section: Introductionmentioning
confidence: 99%
“…These methods require multiple, time-consuming centrifugation steps to remove cellular debris and other interferences, causing sample preparation to become a major bottleneck in the bioanalytical workflow. Clark et al demonstrated the rapid extraction and preconcentration of DNA using MIL solvents in dispersive and single droplet extraction methods [104]. Following MILbased extraction of plasmid DNA (pDNA) from bacterial cell lysate, the nucleic acid was sufficiently pure for PCR amplification.…”
Section: Biological Applications Of Milsmentioning
confidence: 99%